THE EFFECT OF LIQUIDITY AND LEVERAGE ON COMPANY VALUE WITH PROFITABILITY AS A MEDIATING VARIABLE ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2017-2019 - Diana Krismunita; Imronudin Imronudin (Journal of Management and Islamic Finance, 2021)
This study aims to determine the effect of Liquidity, Leverage on Company Value with Profitability as a mediating variable. The sample of this study was a manufacturing company listed on the Indonesia Stock Exchange by using purposive sampling method. There are 66 manufacturing companies selected for three years, so the total sample was 198. This study applied secondary data from annual reports. This research was a quantitative research using panel data regression and path analysis using Eviews software. The results of this study indicate that the current ratio has no effect on return on assets, debt to equity ratio has a negative and significant effect on return on assets, return on assets has a positive effect on price to book value, current ratio has a positive effect on price to book value, debt to equity ratio has a positive effect on price to book value, return on assets does not mediate the effect of the current ratio on price to book value, but return on assets mediates the effect of debt to equity ratio on price to book value.